Enhancing federal inter-governmental relations and state building in Somalia - Hashi, Mohamed Bile; Barasa, Tiberius
Federalism is regarded as the ideal strategy for Somalia in forming a power-sharing agreement among Somali clans and a workable solution to the national unity, peace and security. Despite the adoption of federalism in Somalia, the reality on the ground is different as Somalia has continued to be in a state of political quandary. Available literature says little about the Inter-Governmental Relations (IGR) and civic state building as a possible cause of political quandary. This study explores Somalia’s Federal-state Inter-Governmental Relations and civic state building. It seeks to answer the question, how and to what extent have the intergovernmental relations between the federal government and federal member states affect civic state building in Somalia? Utilizing a qualitative approach specifically, synthesis of literature, in-depth interviews and guided questionnaire, the study suggests that despite the existence of a federal structure, intergovernmental relations between the federal government and the member states have been characterized by tensions and conflicts; the federal and state apparatuses lack appropriate provisions in the constitution and that the minimal federal-state IGR laws that are now in place are not honored and applied by both levels of the federal government. This study also suggests that there is no effective, agreed-upon model of IGRs and power sharing in Somalia between the federal government and member states, thus constraining any kind of progression in the federal institutions. This study also shows how dangerous it is to neglect indigenous approaches of state building that take into account Somali culture, religion, and customs. The findings of this study contributes to the scholarly discourse on civic state-building, federalism, and IGRs in post-conflict settings. This study recommends a review of the federal-state intergovernmental relations laws paying attention to cultural and religious significance, to strengthen federal-state IGRs.